If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = x + (-6) -10 = x + -6 Reorder the terms: -10 = -6 + x Solving -10 = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + -1x = -6 + x + -1x Combine like terms: x + -1x = 0 -10 + -1x = -6 + 0 -10 + -1x = -6 Add '10' to each side of the equation. -10 + 10 + -1x = -6 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = -6 + 10 -1x = -6 + 10 Combine like terms: -6 + 10 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4
| 1/4(60+12d)=15+4d | | -14+y=-26 | | 6(7b+8)=-204 | | -2x(x)=x-1 | | 79+3x+12=125 | | 5p-18(4)=-36 | | -4(-3+4v)=124 | | 2/3x+3/5=2-2/5x | | -2x=x-1 | | 56+91919=g | | 79+3x+2=125 | | -8m-16+3m+9= | | 56+91919= | | 2(a+1)=9+a+1 | | 2(6x+3)=4x+4+8x+2 | | 2x+3x+8=82 | | -6(5+8v)=-22 | | -21+x=10 | | 1-8(3d-2)=1-4(d+5) | | -6x-5(2x+6)=98 | | 3(x-6)=42 | | -7(p-8)=21 | | 15=x-(-8) | | Ln(x)+ln(3x-1)=0 | | 3/5x=-7 | | 3x(-19x)=(-2x)+7 | | 2m-5=1-3(2m-12) | | Y=-8+6(x-2) | | 5(x+2)-3(x+4)=26 | | 1-12+3-8y=5-12+5-8y | | x+(x*0.62)=100 | | 5(x-2)=2(x+2) |